artificial intelligence: implications in the customer journey artificial intelligence & chatbots : implications in the customer experience - Valentine, Dosne (2022)
Artificial Intelligence is humankind's most dominant "weapon" to transform the retail industry. "How AI will shape a new era for seamless customer journeys" defines the critical research question. The rise of digital interfaces enforced by the Covid-19 pandemic, emerging technologies, and the big data revolution represents the preeminent drivers to disrupt AI adoption towards a new era of customer experience in the retail landscape. This work project investigates how AI technologies revolutionize the banking industry impacted by chatbots towards rethought customer engagement among financial services. Further explores the consequences throughout the supply chain workflow and the role of sustainability by shaping the AI future world.